2006
DOI: 10.1111/j.1745-7254.2006.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of tanshinone IIA to UW solution decreases skeletal muscle ischemia-reperfusion injury1

Abstract: UW plus tanshinone IIA increased protection against I/R injury, suggesting that tanshinone IIA has clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Wang et al, 2006;J.J. Liu et al, 2006), however, also concentrations of 3 g/mL in vitro or 0.05 to 0.2 g/mL in vivo were reported to protect cells from free radicals induced apoptosis (Meng et al, 2006;H.G. Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Wang et al, 2006;J.J. Liu et al, 2006), however, also concentrations of 3 g/mL in vitro or 0.05 to 0.2 g/mL in vivo were reported to protect cells from free radicals induced apoptosis (Meng et al, 2006;H.G. Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…11,12 Before induction of anaesthesia for the experiment, each rat was subjected to 12 h of fasting with unrestricted access to water. Rats were anaesthetized with 3% pentobarbital (40 mg/kg intraperitoneally) and then kept on a heated operating table to maintain core body temperature at 36.5 -37.5 ºC, monitored with a rectal temperature probe.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…Recent medical research has found more than 15 types of chemical structures extracted from DS, and tanshinone IIA was the main effective components of anti-oxidative activity (22), adjustment of the metabolism of blood lipids (23), improvement of rheology, body microcirculation and activity of fibrinolysis (24). Investigators have reported that tanshinone IIA displayed significant protective effects on I/R injury in skeletal muscle preservation (9). In this study, we found that tanshinone IIA down-regulated the quantity of MDA and up-regulated the activity of SOD in preserved renal tissues, which revealed the anti-oxidant activity of tanshinone IIA.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have proven that tanshinone IIA is one of the most abundant components of DS, exhibiting a variety of biochemical activities, including vasorelaxation, elimination of oxygen-derived free radicals, stabilization of vascular endothelial function and protection against I/R injury (8). Investigators have reported that tanshinone IIA improves the protective effects of University of Wisconsin (UW) solution for skeletal muscle preservation by inhibiting ICAM-1 expression and apoptosis (9). In this study, tanshinone IIA was added to the standard hypothermia preservation solution in order to investigate a possible protective effect of tanshinone IIA during hypothermic preservation and explore the possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%